Xenogeneic Islet Transplantation of Ad5F35-SOCS1 Infected Islets for Therapy of Diabetes - Suo, G. J.; Zhao, Z. X. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Islet transplantation is the most important approach for treating type I diabetes (T1DM), but the early islet apoptosis limits the therapeutic efficacy. SOCS1 (suppressor of cytokine signaling 1), not only has an effect on cytokine signaling pathway, it is also involved in the regulation of signal transduction pathway in cell apoptosis. The aim of this study was to investigate the effect of overexpression of suppressor of cytokine signaling 1 (SOCS1) in islet grafts. In this paper, the Ad5F35-SOCS1 infected islets were constructed, meanwhile the diabetic mice were established and the xenogenic islet transplantation was performed. After islet transplantation, the blood glucose levels of islet recipients were monitored and the kidney samples were harvested to perform the histological and apoptosis assay. The results showed that the blood glucose was restored in most of the diabetic mice after Ad5F35-SOCS1 infected islets transplantation, and normoglycaemia was maintained for a long time. Furthermore, histological analysis indicated that the infected grafts with overexpression of SOCS1 showed strong insulin secretion function and decreased apoptosis in the early post-transplant period. These results demonstrate that SOCS1 could be the underlying target molecule in islet therapy which has great clinical and practical significance.
Keywords: Ad5F35-SOCS1; islet transplantation; xenogenic transplantation